Perspective and update: intrapleural fibrinolytic therapy for pleural infections and other forms of pleural organization - Torry A. Tucker; Andrey A. Komissarov; Steven Idell (Respiratory Research)
Abstract Intrapleural fibrinolytic therapy (IPFT), also known as intrapleural enzymatic therapy (IET), has been utilized for decades to treat pleural infections by expediting drainage in patients with pleural organization. The successful MIST2 trial demonstrated that IPFT improves pleural opacification, reduces hospital stays, and decreases short-term surgical referrals. Despite significant progress, gaps remain in identification of the optimal fibrinolytic agents, dosing, and safety improvements. IPFT is generally recommended for patients with loculation and failed pleural drainage, with a consensus panel advocating for combined tissue plasminogen activator (tPA) and DNase therapy. How each agent may affect the activity or function of the other in the combination remains unclear. While IPFT can reduce the need for surgical intervention, there are relatively few comparative clinical trials to guide initial therapy. Emerging low-dose IPFT treatment approaches may benefit patients who are poor surgical candidates. Personalized IPFT candidate approaches, such as the Fibrinolytic Potential Assay (FPA), could refine dosing and improve outcomes. Additionally, biomarkers like pleural fluid PAI-1 and suPAR concentrations may predict clinical outcomes and guide treatment. New therapeutic agents, including PAI-1 inhibiting peptides and mesothelial profibrogenic targets, are under investigation to enhance IPFT efficacy. These advances hold promise for improving the management of pleural infections and other forms of pleural organization.